أثر الثقافة المتكیفة على محددات سلوك المواطنة التنظیمیة دراسة میدانیة على عینة من مؤسسات دباغة الجلود بالجزائر - بن عودة مصطفى (Finance and Business Economies Review, 2018)
This study dealt with the issue of the impact of Adaptive culture on the determinants of organizational citizenship behavior, and this study has been chosen in the leather industry, represented by seven tanneries of the largest and oldest tanneries operating in this sector in Algeria. Four public and three private tanneries. The study was applied to a sample of (142) employees, out of a study population of (714) employees. The study used a questionnaire as a key tool for gathering information and data as well as personal interviews The questionnaire was distributed randomly on various workers in the leather tanning institutions, and so on different organizational levels, The study concluded to a set of results including the following:  The high level of awareness of the Adaptive culture among workers in the leather tanning institutions.  The high level of awareness of all the determinants of organizational citizenship behavior (organizational loyalty, organizational justice, administrative leadership) as we noticed high levels, except two determinants (job satisfaction, organizational support), in which we noticed medium levels.  .The study showed through the simple linear regression results that there is a statistically significant positive effect at α level (α ≤ 0.01), between the Adaptive culture and organizational citizenship behavior determinants among workers in the leather tanning institutions